Evaluation of Water Resources Carrying Capacity in Heilongjiang Province Based on PSO-SVM Model - WANG Tao; LI Zhijun (Renmin Zhujiang)
The problem of water resources has triggered a global crisis.With the rapid development of the social economy,the rapid increase in population,and the acceleration of modernization and urbanization,the demand for water in various industries is gradually increasing,and the problems of water shortage and water waste are becoming serious.Heilongjiang Province is an important industrial base and a major grain-producing province in China.With the rapid development of the economy and society,the contradiction between the supply and demand of water resources has become increasingly prominent.Although many measures have been taken to protect water resources in Heilongjiang Province,the development and utilization situation of water resources is still severe.In view of the above problems,this paper established a support vector machine (SVM) model optimized by particle swarm optimization (PSO) algorithm to evaluate the water resources carrying capacity in Heilongjiang Province.Based on the actual situation of Heilongjiang Province,an evaluation index system and index grading standards were established to evaluate the water resources carrying capacity of 13 cities in Heilongjiang Province in 2020.It thus provides a reference for the development and utilization of water resources in the future and plays a certain role in the application and promotion of SVM in water resources.The PSO-SVM model complements the theory of multi-factor comprehensive evaluation.